A New Maximum Power Point Tracking Method Based on Power Electronics for Solar PV Applications (International Journal of Food and Nutritional Sciences, 2021)
False MPP was produced because the conductivity of the solar cell changed nonlinearly with different atmospheric variables.The proposed method is trained with a neural network to get around this issue.Although incremental conductance can provide slightly superior overall performance in cases of rapidly changing atmospheric circumstances, the algorithm's accelerated complexity will necessitate larger, more expensive hardware, giving it an edge over MPPT only in large PV arrays. Lack of knowledge of the obligation cycle variation is a weakness of the fuzzy logic technique, which leads to a suitable accuracy level with poor dynamic properties. The PWM approach is used to solve the issue, and the corresponding duty cycle is changed to activate the inverter